The Speaking Training Using Cocomelon Youtube Channel for Students in SEPAMA Cambodia - Veronika Unun Pratiwi (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
Abstrak: Bahasa Inggris adalah bahasa dunia. Artinya, bahasa Inggris diajarkan sebagai bahasa asing di banyak negara, termasuk Kamboja, dan untuk alasan ini. Semua industri mengalami dampak negatif dari epidemi ini, termasuk pendidikan, yang digunakan untuk memiliki kelas tatap muka menjadi diperlukan secara online atau di ruang kelas virtual. Berbicara melibatkan terlibat dengan bahasa tertulis yang telah dikodekan. Keterampilan berbahasa oral secara langsung terkait dengan kemampuan mengarahkan.Kurang siswa di Kamboja belajar bahasa Inggris sebelumnya. Di Indonesia, bahasa Inggris adalah salah satu bahasa asing yang ditawarkan. Tim yang berdedikasi dari Universitas Veteran Bangun Nusantara melatih siswa kelas delapan dalam penggunaan aplikasi Cocomelon Youtube Channel karena pentingnya materi berbicara bagi siswa. Kata Kunci: Bahasa Inggris, Berbicara, Cocomelon Youtube Channel Abstract: The worldwide language is English. That is, English is taught as a foreign language in many nations, including Cambodia, and for this reason. All industries are being negatively impacted by this epidemic, including education, which is used to having face-to-face classes become required online or in virtual classrooms. Speaking involves engaging with written language that has been encoded. Oral language proficiency is directly correlated with heading ability.Less pupils in Cambodia were learning English before. In Cambodia, English is one of the foreign languages offered. The Veteran University of Bangun Nusantara dedicated team trains eighth-graders in the use of the Cocomelon Youtube Channel application due to the significance of speaking material for pupils contains the issue and focus of dedication, dedication objectives, dedication research methods / approaches / strategies, and community service results. Keywords: English, Speaking, Cocomelon Youtube Channel